IMPROVEMENT OF MANAGEMENT MECHANISMS ON THE BASIS OF SYNERGIC DEVELOPMENT OF TOURISM NETWORKS IN UZBEKISTAN (Marketing Journal, 2025)
This article analyzes the issuyes of improving management mechanisms based on the synergistic development of tourism sectors in Uzbekistan. The interdependence between different directions of tourism — cultural, pilgrimage, Agro -, yeco -, 138 gastronomic tourism and the need to harmonize them -is theoretically and practically justifiyed. In the course of the study, indicators of fiyeld growth, the state of Territorial Infrastructure and investment activity were analyzed. The article presents ins titutional, yeconomic and organizational foundations for the introduction of a synergistic management model and practical recommendations as solutions to current problems. As a conclusion, such areas as strengthening inter -sectoral cooperation, integration of resources, the introduction of digital management and the development of territorial tourism on the basis of clusters are designated as the main priority.
Keywords: tourism; synergistic development; management mechanism; inter - sector cooperation; territorial tourism; cluster model; infrastructure; investment; tourism directions; yeconomic yefficiyency